To Gain Competitive Advantage through Supply Chain Management : A Case Study of Texas Instruments - Pan, Yan (2013)
Globalization has brought fundamental change in the world economy over the last three decades. It has shifted the world economy towards an integrated and interdependent one. From businesses’ perspectives,globalization has double effects. On the one side, the process has produced many opportunities. Firms are exposed to a much larger market. Therefore, they can reduce costs for their products by producing in countries where key inputs, such as raw material, labor, are cheap, while increasing profit margins by selling their products around the world. On the other side, the process of globalization has also created new threats for companies as the entry of foreign companies increases competition and drives down prices. The companies accustomed to dominating their domestic markets now have to face intense competition from both inside and outside their own countries (Hill, 2011). Under this dynamic market environment, companies keep changing their business strategies to meet the diverse customer needs in order to survive and stay competitive. Manufacturers are re-engineering their production processes and restructuring internal information and operating systems to lower costs. More and more companies begin to source raw materials globally and set up factories in locations around the world to take advantage of national differences in production factors such as labor, land, energy, to reduce production costs and improve quality. At the same time, it becomes a common practice for companies to outsource the production of component parts and services to independent suppliers. With the rapid development of communication, information processing and transportation technology, companies’ business networks extend globally and their value chain becomes more complex by forming cooperative partnerships or strategic alliances with other companies vertically or horizontally. At the same time, product life cycle continues to shrink with new products keep emerging, existing products become obsolete more rapidly. The phenomenon is more evident in the high tech semiconductor industry, where technological advances have shortened product life cycles of some semiconductors to one or two years (TI’s Form 10-K annual report, 2011). Shrinking product life cycle has several implications for manufacturers: first, short product life cycle means that innovative products provide just a short term competitive advantage. Technology which is a competitive edge today may become obsolete several months later. Companies have to innovate consistently to stay competitive. Second, in order to leverage the short term competitive advantage the product may provide, companies need to reduce the manufacturing cycle times and order fulfillment lead time. Third, companies need to be agile to meet the changing customer needs. Finally, inventory management becomes critical for business success. On the one side, if companies keep too many inventories in advance for anticipated customer demand that never materializes, they will face the risk of inventory obsolescence. On the other side, if companies underestimate customer demand, they may lose market share and miss the opportunity to increase their revenue. The main purpose of the dissertation is to explore how SCM could be used as a source of competitive advantage for a company in the dynamic business environment. A leading semiconductor company Texas Instruments (TI) is chosen as the case in this dissertation.